(untitled) (Medical Forum Monthly, 2022)
Objective: To assess challenges and success in attaining the health related Millennium Development Goals (MDG 4, 5 & 6) in developing countries. Study Design: A systematic review Place and Duration of Study: This study was conducted at the Agha Khan University from April to September 2018. Materials and Methods: Systematic search for published literature using search term Challenges, Successes, Achieving, Health related MDGs and Developing countries. Data bases like Pub-Med, Science direct and Google Scholars were used to search the studies. Eligibility criteria were set to select the article for review. Filters for article type, free full text, years of publication were applied for more focused review.​ Results: Systematic review finding revealed that weak governance, lack of strategic leadership, financial constraints and low budget allocation and lack of human resource for health capacity were identified as the most documented challenges. Among successes it includes multi-sectoral approach, increased health service package, increased health service coverage, and poverty reduction strategies. ​ Conclusion: ​Systematic review findings present a complex picture of progress towards health related MDGs. Results clearly indicate that reducing maternal and child health related indicators are merely not a technical process but interplay of several non-health determinants including poverty, socioeconomic disparities, health inequities along with leadership and governance.